Attributes of cassava varieties desired by farmers in subSaharan Africa - Nweke, F.; Dixon, A.; Asiedu, Robert; Folayan, S.A. (1994)
Manihot esculenta.This paper which is based on information collected as part of Collaborative Study of Cassava in Africa (COSCA) provides information on cassava genotypes cultivated in sub-Saharan Africa. It shows that there is a high degree of turnover in the cassava genotypes cultivated. Farmers abandon the cultivation of genotypes which do not meet their need, they introduce better genotypes into their cropping systems whenever such are available to them. The attributes which the farmers desire in the cassava genotypes are discussed. The performance of the presently cultivated genotypes, in terms of root yield, earliness, suitability for intercropping and postharvest qualities are assessed; Varieties; Agronomic characters; Yield components; Roots; Intercropping; Processed products; Quality; Africa South of Sahara Manihot esculenta; Variedades; Características agronómicas; Caracteres de rendimiento; Raíces; Cultivo intercalado; Productos procesados; Calidad; Africa al sur del Sahara Cassava; Yuca; Genética vegetal y fitomejoramiento; Cultivo; Articles in proceedings; Artículos en memorias; Arregloy sistemas de cultivo Plant genetics and breeding; Crop husbandry; Cropping patterns and systems.